Technoeconomic analysis of broccoli biorefineries for polyphenol extraction and biobutanol production - Frausto-Torres, Luis Gerardo; Vázquez-Núñez, Édgar; Molina-Guerrero, Caros Eduardo (Renewable Energy, Biomass & Sustainability, 2022)
Fossil resources dominate the energy supply. In 2019, the total energy supply worldwide accounted for 606 exajoules (EJ), of which fossil fuels (oil, coal, and gas) had a share of 81% (490 EJ). The biorefinery concept proposes the synthesis of renewable energies as an alternative to fossil carburants. As a second-generation biofuel, biobutanol has outstanding characteristics and can be obtained from agricultural residues and organic wastes; however, its bioprocessing is not economically feasible using current methodologies. In 2021, the global production of broccoli (Brassica oleracea var. Italica) was 25.5 million tons; being the fifth top producer, Mexico generated 687,000 tons of this vegetable. In this work we propose a production design for the synthesis of biobutanol and the recovery of valuable byproducts, like high-value polyphenolic compounds, from broccoli residues, abundant in the state of Guanajuato, Mexico. For the transformation of the substrate a biochemical matrix was proposed for its composition, as well as a biotechnological route that follows a general path with the acid pretreatment of biomass, enzymatic hydrolysis, and acetone-biobutanol-ethanol (ABE) fermentation using anaerobic bacteria. The outlined biorefinery integrates conventional methods in three methodological pathways and a hybrid model for the downstream process. With the aim of visualizing the global economic performance and evaluating a possible reduction in production costs, we performed a technoeconomic analysis of the designed second generation biorefinery plant. The economic evaluation was carried out using SuperPro Designer® V 12.0. The results confirm the enormous dependence that this type of biorefinery suffers from energy demands. We found that by implementing strategic adaptations to the downstream process operating costs can be considerably reduced. However, to achieve full financial efficiency in the production of biobutanol from broccoli residues, it is necessary to deepen the research and development of innovative methods to efficiently separate and purify the final products, as well as novel methodologies for the biotransformation of the described lignocellulosic biomass along the entire technological route. We also found that there is a large opportunity in the valorization of the plentiful broccoli residues generated in the Guanajuato region.